THE GREEK INSCRIPTIONS OF THE SARDIS SYNAGOGUE - Kroll, John H. (Harvard theological review, 2001)
Since its discovery and excavation in the 1960s, the Synagogue at Sardis has taken its place as the most significant monument of diaspora Judaism in Roman Asia Minor.For their assistance and involvement with this study, I especially wish to thank Marianne Bonz, Katherine Kiefer, David Mitten, Andrew Seager, Jane Scott, Thomas Kraabel, and L. Michael White, and Walter Ameling. Notable for its size, richness, basilical form, and prominent location within the city, the Synagogue is exceptional also for the more than eighty inscriptions recovered from its interior. With the exception of six fragments in Hebrew,To be published by Frank M. Cross in the final Synagogue volume. The Hebrew texts, all inscribed on fragments of marble wall revetment, give the words, “Peace (Shalom)” (Hanfmann 1972, fig. 86; Seager and Kraabel 1983, 171, fig. 269) and “vow” (twice each), and two proper names, Yohanan and Severus (formerly read as “Verus” [Hanfmann 1967, 25, n. 25; Seager and Kraabel 1983, 171, 179, n. 9]). the inscriptions are in Greek and for the most part commemorate members of the congregation who contributed the many elements of interior decoration: the mosaics on the floor, the marbling of the walls, and a number of architectural and ritual furnishings.